2011
DOI: 10.1007/s10901-011-9232-y
|View full text |Cite
|
Sign up to set email alerts
|

High dwelling vacancy rate and high prices of housing in Malta a mediterranean phenomenon

Abstract: Current data from South European countries, especially Malta, indicates the existence of some contradictory forces in the housing market that defy the law of supply and demand and require explanation. In a 'normal' housing market, it can be expected that a high dwelling vacancy rate would help keep down the price of housing. In Malta, however, both the vacancy rate and housing prices have been rising in tandem for decades, unabated, even under the recent international market crunch. The government housing poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…Intuitively, with Malta been regarded as one of the world’s most densely populated country and given the favourable economic outlook, significant economic expansion relative to its housing sector is unavoidable. The works of Bianco (2006), Vakili-Zad (2006); Darmanin (2008), Camilleri (2011); Vakili-Zad and Hoekstra (2011), Falzon and Bezzina (2013); Falzon and Lanzon (2013) and Micallef (2018) are among the existing studies on the real estate and housing market in Malta. Interestingly, Bianco (2006) examined the housing and real estate market of Malta as the country gained European Union (EU) accession.…”
Section: The Housing Market Studies: Review Of Extant Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Intuitively, with Malta been regarded as one of the world’s most densely populated country and given the favourable economic outlook, significant economic expansion relative to its housing sector is unavoidable. The works of Bianco (2006), Vakili-Zad (2006); Darmanin (2008), Camilleri (2011); Vakili-Zad and Hoekstra (2011), Falzon and Bezzina (2013); Falzon and Lanzon (2013) and Micallef (2018) are among the existing studies on the real estate and housing market in Malta. Interestingly, Bianco (2006) examined the housing and real estate market of Malta as the country gained European Union (EU) accession.…”
Section: The Housing Market Studies: Review Of Extant Literaturementioning
confidence: 99%
“…Using an experimental year of 1980 to 2005 (far below the span year of the current study, 2005Q1-2016Q4), Bianco (2006) expressed the importance of environmental planning awareness, residential typologies, and the built and new aesthetic to the housing and real estate market. Also, in their study of the Malta’s housing dynamics, Vakili-Zad and Hoekstra (2011) empirically observed the age-long and unusual tandem of vacancy rate of dwellings and housing prices. The study maintained that the housing market in Malta is such that exhibits some contradictory forces which obviously defy the law of demand and supply.…”
Section: The Housing Market Studies: Review Of Extant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Kwoun et al (2013) analyzed cycles of unsold new housing stocks (UNHS), housing investment, and housing supply-demand by introducing system dynamics to determine the dynamics of the housing market and the importance of UNHS as a potential indicator of housing investment, supply and price [3]. Vakili-Zad et al (2011) explain the major factors contributing to the unlikely combination of a high vacancy rate and the high price of housing from a welfare state perspective [13]. Couch et al (2013) explored the relationships between shrinking cities, housing vacancy and policy responses in Liverpool, UK.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some special circumstances may be neglected in selecting samples, resulting in large errors in the survey results. An indicator of HVR is often used by countries in the West as a weathervane to indicate the state of supply and demand in the real estate market (Ortalo-Magné and Rady, 2006); it is regarded as one of the main bases for real estate regulation and control (Vakili-Zad and Hoekstra, 2011). Academic research on housing vacancy on the West is also systematic, covering the concept of housing vacancy (Couch and Cocks, 2013;Molloy, 2016), vacancy rate calculation, and relationships such as those between housing vacancy and socio-economic indicators or between the real estate market and vacancy rate (Gentili and Hoekstra, 2019).…”
Section: Introductionmentioning
confidence: 99%